2011
DOI: 10.1590/s0102-695x2011005000089
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Amaryllidaceae alkaloids from Zephyranthes grandiflora by GC/MS and their cholinesterase activity

Abstract: Amaryllidaceae are known as ornamental plants, furthermore some species of this family contain galanthamine, an acetylcholinesterase inhibitor approved for the treatment of Alzheimer´s disease, and other alkaloids with interesting pharmacological activity. The chemical composition of alkaloids from Zephyranthes grandiflora Lindl. was analyzed by GC/MS. Seven known compounds, belonging to five structural types of Amaryllidaceae alkaloids, were identified. The alkaloid extract from the bulbs showed promising cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…En el caso de Z. concolor y Z. robusta hay evidencia de la biosíntesis de galantamina (Reyes-Chilpa et al, 2011). En el caso de Z. carinata, ya se han registrado alcaloides como licorina, galantina y haemantamina; alcaloides de interés para el tratamiento de la leucemia (Cahlíková et al, 2011).…”
Section: F Género Zephyranthesunclassified
“…En el caso de Z. concolor y Z. robusta hay evidencia de la biosíntesis de galantamina (Reyes-Chilpa et al, 2011). En el caso de Z. carinata, ya se han registrado alcaloides como licorina, galantina y haemantamina; alcaloides de interés para el tratamiento de la leucemia (Cahlíková et al, 2011).…”
Section: F Género Zephyranthesunclassified
“…Compounds mainly alkaloids were identified on the basis of their characteristic mass fragmentation pattern. Reports showing GC/MS based chemical profiling, identified galanthamine, lycoramine, vittatine, nerbowdine, haemanthamine, tazettine, galanthine in bulbs of Z. robusta and galanthamine, lycoramine, vittatine, nerbowdine, haemanthamine, tazettine, galanthine in bulbs of Z. grandiflora [47][48]. However, chemical profiling of Z. grandiflora bulbs by UPLC/MS identified AAs: lycorine, lycoramine, dihydrovittatine, lycoramine-N-oxide, galanthine, hamayne, zaiden, ambelline, crinamidine, haemanthamine, vittatine, zefbetaine, ungeremine, 1-O-(3-hydroxybutyryl)-pancratistatin, tortuosine [49].…”
Section: Traditional Usagementioning
confidence: 99%
“…The alkaloids chlidanthine, galanthamine, galanthamine-N-oxide showed poor inhibitory activity of HIV-1 replication and cytotoxicity against human MT-4 cells [42]. In 2011 Cahlikova et al, reported the promising cholinesterase inhibitory activities of alkaloid extract of bulbs of Z. grandiflora against human blood acetylcholinesterase and human plasma butyrylcholinesterase [48]. 8-O-demethylmaritidine, alkaloid from Z. robusta Baker showed significant acetylcholinesterase inhibition activity and indicates that this activity is mainly related with galanthamine-and lycorine-type skeleton and galanthamine type skeleton are more active inhibitor than other skeletons of AAs.…”
Section: Acetylcholinesterase Activitymentioning
confidence: 99%
“…All these alkaloids contain the quinoline and isoquinoline nucleus. [3,[7][8][9][10][11][12][13][14][15][16].…”
mentioning
confidence: 99%